2018
DOI: 10.7150/thno.24747
|View full text |Cite
|
Sign up to set email alerts
|

Neurogliovascular dysfunction in a model of repeated traumatic brain injury

Abstract: Traumatic brain injury (TBI) research has focused on moderate to severe injuries as their outcomes are significantly worse than those of a mild TBI (mTBI). However, recent epidemiological evidence has indicated that a series of even mild TBIs greatly increases the risk of neurodegenerative and psychiatric disorders. Neuropathological studies of repeated TBI have identified changes in neuronal ionic concentrations, axonal injury, and cytoskeletal damage as important determinants of later life neurological and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 55 publications
2
23
1
Order By: Relevance
“…In the context of TBI, markers of senescence have been shown to elevate in microglia and astrocytes following a controlled cortical impact protocol [153]. Contrary to studies showing vascular dysfunction in mTBI [2, 157], we did not see evidence of cellular senescence in endothelial cells. Furthermore, we did not specifically evaluate senescent microglia in this cohort.…”
Section: Discussioncontrasting
confidence: 98%
“…In the context of TBI, markers of senescence have been shown to elevate in microglia and astrocytes following a controlled cortical impact protocol [153]. Contrary to studies showing vascular dysfunction in mTBI [2, 157], we did not see evidence of cellular senescence in endothelial cells. Furthermore, we did not specifically evaluate senescent microglia in this cohort.…”
Section: Discussioncontrasting
confidence: 98%
“…The co-expression of CD-90 and CD-105 confirmed the long-term survival of hUCMSCs. Moreover, as representative markers of newborn neurons (DCX) and mature neurons (NeuN), the immunohistochemical results confirmed that hUCMSCs implantation enhanced regeneration of neuronal tissue under the shelter of scaffolds in CB group 40 . Indicating that collagen/silk fibroin scaffolds may create a favorable microenvironment for the survival and oriented differentiation of seed cells.…”
Section: Discussionmentioning
confidence: 65%
“…After inducing repeated mild TBI in mice expressing ChR2, Adams et al measured neuronal function through bilateral intracranial electrophysiological recordings in response to optogenetic photostimulation. They found that this photostimulation resulted in reduced evoked neuronal response and neuronal functional deficits, in both pericontusional tissue and in tissue in the contralateral hemisphere [102]. This study thus represents the first in-situ application of optogenetic photostimulation as a tool for TBI treatment and analysis.…”
Section: Optogenetics For the Study And Treatment Of Tbimentioning
confidence: 63%